REFORMING LAND RELATIONS IN CHINA AND VIETNAM: EXPERIENCE FOR UKRAINE - Petruk O.V. (Pressing Problems of Public Administration, 2016)
The article described the legal model of land reform in China and Vietnam, on the basis of which offeredpractical recommendations for the improvement of land relations in Ukraine